Why Do Self-Employed Immigrants in Denmark and Sweden Have Such Low Incomes? - Pernilla Andersson; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2004)
When studying income differences and income distribution, the self-employed are often excluded from the population studied. There are several good reasons for this, for example that incomes from self-employment are not reported to the same extent as incomes from being an employee. On the other hand it is a problem to exclude the self-employed when studying income differences if the group is large, if the share that is self-employed differs between groups and if there is a difference in the average income from self-employment compared to the average wage income. This is the case when we study incomes for immigrants in Western Europe. The immigrants are overrepresented among the selfemployed, self-employed immigrants are in other sectors than self-employed natives, and the incomes from self-employment differ from the incomes of the wage earners. In this paper we look at the incomes for the self-employed in Denmark and Sweden. To minimize the problems with unreported income we will mainly compare the annual incomes of the selfemployed immigrants and their native counterparts. The measurement error should only create a bias in the estimate of the income difference between the groups if there is a systematic difference in how they report their incomes. Using two cross-sections, one for each country, we find large income differences between natives and immigrants in both countries. Regression estimates show that most characteristics have the same influence in the two countries but also some interesting differences. Using quantile regressions we find that the difference in annual incomes differs depending on where in the income distribution we look. We find that the difference is smaller higher up in the distribution.
Keywords: J23; J15; J61; 330; immigrant workers; self-employment; quantile regressions; income differences; Selbstständige; Einkommensverteilung; Migranten; Schätzung; Dänemark; Schweden